Metagenomic insight of nitrogen metabolism in a tannery wastewater treatment plant bioaugmented with the microbial consortium BM-S-1. Issue 13 (9th November 2016) - Sul, Woo-Jun; Kim, In-Soo; Ekpeghere, Kalu I.; Song, Bongkeun; Kim, Bong-Soo; Kim, Hong-Gi; Kim, Jong-Tae; Koh, Sung-Cheol
ABSTRACT: Nitrogen (N) removal in a tannery wastewater treatment plant was significantly enhanced by the bioaugmentation of the novel consortium BM-S-1. In order to identify dominant taxa responsible for N metabolisms in the different stages of the treatment process, Illumina MiSeq Sequencer was used to conduct metagenome sequencing of the microbial communities in the different stages of treatment system, including influent (I), buffering (B), primary aeration (PA), secondary aeration (SA) and sludge digestion (SD). Based on MG-RAST analysis, the dominant phyla were Proteobacteria, Bacteroidetes and Firmicutes in B, PA, SA and SD, whereas Firmicutes was the most dominant in I before augmentation. The augmentation increased the abundance of the denitrification genes found in the genera such as Ralstonia ( nirS, norB and nosZ ), Pseudomonas ( narG, nirS and norB ) and Escherichia ( narG ) in B and PA. In addition, Bacteroides, Geobacter, Porphyromonas and Wolinella carrying nrfA gene encoding dissimilatory nitrate reduction to ammonium were abundantly present in B and PA. This was corroborated with the higher total N removal in these two stages. Thus, metagenomic analysis was able to identify the dominant taxa responsible for dissimilatory N metabolisms in the tannery wastewater treatment system undergoing bioaugmentation. This metagenomic insight into the nitrogen metabolism will contribute to a successful monitoring and operation of the eco-friendly tannery wastewater treatment system.